2001
DOI: 10.2527/2001.7961549x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory response, growth, and thyroid hormone concentrations are affected by long-term boron supplementation in gilts.

Abstract: An experiment was conducted to determine the long-term effects of dietary boron (B) on growth performance, immune function, and plasma and serum characteristics in gilts. Fifty weanling gilts were allotted to 10 pens based on weaning weight and litter origin. Pens were randomly assigned to receive one of two dietary treatments. Treatments consisted of a basal diet low in B (control) and the basal diet supplemented with 5 mg B/kg diet as sodium borate. Gilts remained on their respective experimental diets and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 30 publications
3
52
2
Order By: Relevance
“…Although Armstrong et al (2001) showed that serum urea nitrogen level was increased by 5 mg/kg supplemental B in growing pigs, in this study 10 mg/kg or higher levels of B were needed to increase serum urea levels.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Although Armstrong et al (2001) showed that serum urea nitrogen level was increased by 5 mg/kg supplemental B in growing pigs, in this study 10 mg/kg or higher levels of B were needed to increase serum urea levels.…”
Section: Discussioncontrasting
confidence: 61%
“…It is reported that B is required for bone (Wilson and Ruszler, 1998), mineral (Hunt, 1989;Eren et al, 2004), lipid (Hall et al, 1989;Naghii and Samman, 1997;Başoğlu et al, 2000) and energy metabolism (Hunt andHerbel, 1991-1992) as well as for immune (Armstrong et al, 2001) and endocrine functions (Beattie and Peace, 1993). Boron reacts with biological substances containing cis-hydroxyl groups that maintain proper cell membrane function or stability, and it influences hormone reception and transmembrane signalling (Nielsen, 1991).…”
mentioning
confidence: 99%
“…Although these results are clear within the limitations of the utilized method, previously reported data raises many doubts about the effect of boron in this regard, where dietary boron supplementation increases production of cytokines following stress, which indicates a role for boron in the immune system. 25 However, these data do not explain the reduction in localized inflammation following an antigen challenge in pigs. 22 Such discrepancy in the behavior of boron may be attributed to the variation in the doses and methods of administration followed during the experiments.…”
Section: Discussionmentioning
confidence: 89%
“…Inconsistent results regarding the effect of boron on body weight were showed in animal studies. Although the supplementation of boron reported to cause weight gain in some studies [6,9], conflicting results were also reported [8,10]. These results are believed to be the results of heterogeneity in type and dosage of the boron compound and duration of the exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the precise role of boron has not been exactly revealed, nutritional intake in human was shown to activate numerous significant inflammatory modifications. Yet, there are still contradictory outcomes on metabolic outcomes both in humans and animals [8,9]. Kucukkurt et al revealed that borax is able to scavenge free oxygen radicals [10].…”
Section: Introductionmentioning
confidence: 99%